Impact of Export-Import Policy Changes on the Local Shrimp Fishing Industry: A Case Study of Shrimp Trade Deregulation in Indonesia - Sidrotun Naim (West Science Business and Management, 2023)
Indonesia's shrimp fishing industry, which is one of the pillars of the country's economy, has undergone a significant transformation driven by changes in import-export policies, including the deregulation of shrimp trade. This study investigates the various impacts of these policy changes on the local shrimp fishing sector. Using a mixed methods approach, we collected and analyzed qualitative and quantitative data. Findings show that trade deregulation has increased shrimp production and employment opportunities. However, income disparities among industry stakeholders and sustainability challenges have emerged. Policy recommendations emphasize the need to balance economic growth with environmental stewardship and income redistribution to ensure a sustainable and equitable future for the shrimp fishing industry in Indonesia.